Land Ownership by Foreign Nationals Through Nominee Agreements: A Comparative Study of Thailand and the Philippines - Lufna Nandita; Muhammad Helmi Fahrozi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The development of the tourism sector in various tourist cities in Indonesia and the surge in investment in the property sector after the COVID-19 pandemic may trigger an increase in interest among foreign nationals to acquire land in Indonesia through nominee agreements. This practice can trigger land ownership disputes between nominees and beneficiary owners, as well as threaten the state's sovereignty over land. This study will examine the legal provisions of nominee agreements and formulate prevention strategies based on comparative studies with Thai and Philippine regulations. This study uses a normative juridical method with a comparative, legislative, and case analysis approach. Data was collected through literature study with qualitative descriptive analysis techniques, using deductive reasoning. This was followed by prescriptive analysis to produce recommendations or practical suggestions as preventive measures against nominee agreement practices in Indonesia. The results of the study show that nominee agreements contradict the objective requirements of agreements, the principle of good faith, and the provisions of the UUPA. This can cause such agreements to be null and void. However, the disharmony between the UUPA and SEMA No. 10 of 2020 causes uncertainty in law enforcement. The weaknesses of the national legal system demonstrate the urgency of imperative regulatory reform. Based on a comparative analysis with Thai and Philippine regulations, it can be seen that both regulations demonstrate the active role of the state in maintaining state sovereignty over land through different mechanisms. By integrating these two regulations into the Indonesian agrarian legal system, it is possible to close loopholes in the law and ensure that land ownership remains under state control.